Little Blue Cattle Louse Solenopotes capillatus (Enderlein) (Insecta: Phthiraptera: Anoplura: Linognathidae) - Kevyn J. Juneau; Phillip E. Kaufman (EDIS, 2009)
EENY-422, a 4-page illustrated fact sheet by Kevyn J. Juneau and Phillip E. Kaufman, is part of the Featured Creatures collection. It describes the smallest of the five sucking lice that feed on cattle, its distribution, description, biology, hosts, economic importance and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.